A statistical comparison between two texts to illustrate the phonetics of Spanish - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2017)
Following an idea proposed by Deterding (2006) for the English version of 'The North Wind and the Sun', this paper compares the standard Spanish version of that fable with an alternative text which corresponds to another fable, 'The Boy who Cried Wolf'. The comparison is based on the phonetic features that appear in both texts, on their phonetic balance, and on the goodness of fit that they display when we compute their phoneme frequencies (and compare those frequencies with an average distribution for Spanish written texts). The conclusion is that 'The Boy who Cried Wolf' seems to perform better than 'The North Wind and the Sun' in all those dimensions.
Keywords: 330; descriptive phonetics; Spanish; phonetic balance; Zipf distribution; Yule distribution